Roman Jakobson et Claude Lévi-Strauss : linguistique et anthropologie structurales - Jacques Durand; Jean-Pierre Albert (Caravelle)
After having briefly recalled the context of his meeting with Jakobson in the United States at the beginning of the 40’s, this article tries to identify what fascinated Lévi-Strauss in the recently discovered Troubetskoy and Jakobson’s phonology. Returning to the notion of phoneme makes it possible to identify, based on the instinctive notion of distinctive sound, a conception of language as a system of differences similar to Saussure’s. Such is the origin of the importance granted by Lévi-Strauss to structural oppositions which he thinks organise the kinship as well as the mythologies. Afterwards, some important results of structural analysis in anthropology are recalled (for example, a new conception of symbolism), in order to evoke the critical impact of Chomsky’s linguistics on this conception of links existing between linguistics and anthropology.